Long-term impacts of hurricanes on mortality among Medicare beneficiaries: evidence from Hurricane Sandy - Keenan, Olivia J.; Soroka, Orysya; Abramson, David; Safford, Monika; Shapiro, Martin F.; Ghosh, Arnab K. (Frontiers in Public Health, 2025)
ObjectivesHurricane-related flooding has long-term socioeconomic effects on impacted areas; however, little is known about the long-term health effects on vulnerable, older residents who remain in impacted neighborhoods. We examined mortality rates among older adults who continued living in ZIP Code Tabulation Areas (ZCTAs) impacted by flooding from Hurricane Sandy for up to 5 years after landfall.MethodsWe conducted a propensity-score matched, ZCTA-level ecological analysis post-Hurricane Sandy across the tri-state area (New York City [NYC], New York state excluding NYC [NY], New Jersey [NJ], and Connecticut [CT]). Using multivariable models, we compared all-cause mortality rates between matched flooded versus non-flooded ZCTAs for up to 5 years after Hurricane Sandy’s landfall, among Medicare fee-for-service (FFS) beneficiaries aged 65 years and older who remained in the same ZCTA from 2013 to 2017. Adjusted mortality rate ratios (aMRR) were estimated for each region, controlling for ZCTA-level demographic and socioeconomic factors informed by the socioecological model of disaster recovery.ResultsBefore matching, compared to non-flooded ZCTAs, flooded ZCTAs had a higher average Area Deprivation Index (ADI) national rank (20.8 vs. 14.8) and a lower average median household income ($71,587 vs. $89,213). In the matched, adjusted analysis, the Medicare FFS beneficiaries who resided and remained in flood-impacted ZCTAs had a 9% higher risk of all-cause mortality up to 5 years after the event compared to the beneficiaries in ZCTAs not impacted by flooding (aMRROVERALL 1.09, 95% CI = 1.06–1.12). Adjusted mortality risk varied across geographic regions. In NYC, ZCTAs impacted by flooding had a significant 8% higher risk of long-term mortality up to 5 years after the event (aMRRNYC 1.08, 95% CI = 1.02–1.15). CT also showed a significant 19% higher risk of long-term mortality up to 5 years (aMRRCT 1.19, 95% CI = 1.09–1.31). However, the results for NJ and NY were not significant (aMRRNJ: 1.01, 95% CI = 0.97–1.06; aMRRNY: 0.96, 95% CI = 0.86–1.07).ConclusionZCTAs impacted by hurricane-related flooding had higher rates of all-cause mortality up to 5 years after the event, but the magnitude of this effect varied by region. These findings highlight the lingering destructive impact of hurricane-related flooding on older adults and underscore the need for long-term, region-specific disaster planning.